Assessment of Agricultural Water Consumption in İzmir Province - Belgin Çakmak; Sertan Avcı (Turkish Journal of Agriculture: Food Science and Technology)
Population growth and the rise in the level of welfare across the world cause an increase in the demand for water, energy and food, while water supply in sufficient quantity and quality is gradually decreasing in parallel. In addition, events such as droughts and floods caused by climate change have negative impacts on ecosystems. In line with the increasing water demand, it is becoming increasingly important to develop sustainable development of water resources, to provide water in the required quantity and quality at the desired place and time, to develop solutions for the effective management of inter-sectoral allocation and to control losses and leakages. Worldwide, the distribution of groundwater and surface water resources by sectors varies between continents over the years and depending on the development of the sectors. When the water consumption rates of domestic (drinking and using), industrial and agricultural sectors, which are the largest users of water resources, are analysed, it is seen that agricultural use is 69%, industrial use is 19% and domestic use is 12% on a global scale. In Turkey, approximately 75% of total water resources are used for agricultural irrigation, while this rate is 33% in Europe. However, the rate of agricultural water use in Southern European countries can reach up to 75%. As is evident, the agricultural sector accounts for the most intensive use of water resources. Agriculture has the most important share in the sustainability of water resources due to its high utilization rate. For this reason, agricultural water use constitutes the main point of ensuring the sustainability of water resources and the most effective use of existing resources. In this study, the basic elements of sustainable urban water management are discussed and a framework for assessing the current water use of Izmir province with a water footprint approach is presented as an example. In addition, a flow chart has been prepared as a basis for the creation of a water footprint map. Such assessments will provide important contributions in terms of ensuring ecosystem sustainability, increasing water efficiency in cities and reducing risks associated with water resources, including food security, and supporting sustainable development.